2016
DOI: 10.1002/pds.4058
|View full text |Cite
|
Sign up to set email alerts
|

Subdural hematoma cases identified through a Danish patient register: diagnosis validity, clinical characteristics, and preadmission antithrombotic drug use

Abstract: Danish patient registers are a useful resource for SDH studies. However, choice of International Classification of Diseases code markedly influences diagnostic validity. Distinction between cSDH and aSDH is not possible based on SDH diagnosis codes only. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…It has previously been shown that the subdural hematoma code used to identify cases in this study is highly valid with a positive predictive value of 96%. 15 This study has several limitations. Even though the approach used in this study enabled the identification of subdural hematoma incident cases with minimal misclassification, it probably resulted in incomplete coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been shown that the subdural hematoma code used to identify cases in this study is highly valid with a positive predictive value of 96%. 15 This study has several limitations. Even though the approach used in this study enabled the identification of subdural hematoma incident cases with minimal misclassification, it probably resulted in incomplete coverage.…”
Section: Discussionmentioning
confidence: 99%
“…15 Use of an antithrombotic drug by the validated cases and their general population controls was assessed for the period from 2000 to 2012 when data were available.…”
Section: Regional Datamentioning
confidence: 99%
“…Chronic subdural hematoma is one of the most frequent diagnoses in neurosurgery 1,2,3 . It is characterized by an intracranial hemorrhage with a history of trauma in 50% of patients and occurs predominantly in males and in the elderly 7,10,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic subdural hematoma (CSDH) is characterized by a chronic deposition of clot in the subdural space, usually with favorable prognosis 1,2 . It is a frequent neurosurgical condition, commonly associated with a previous history of trauma 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation